Changes in food demand in the EU member states and selected OECD countries: the impact of disposable income, unemployment, and inflation - Grodzicki, Tomasz; Jankiewicz, Mateusz (Technological and Economic Development of Economy, 2025)
This study focuses on consumption patterns: as societies get richer, their attitude toward the level and structure of consumption changes. Unemployment and inflation might influence consumption patterns. This paper aims to analyze the impact of unemployment and inflation on the convergence of food demand in households in the EU Member States and selected OECD countries from 1995 to 2019. The analysis of β-conditional convergence proved that the convergence of the share of food expenditure was positively conditioned by the unemployment level and negatively by the disposable income, but with no inflation influence. While in club convergence of more developed economies, with a higher inflation level comes a higher share of disposable income spent on food. First published online 27 November 2025